2017
DOI: 10.1142/s0219749917500381
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tripartite quantum correlations in mixed classical environments: The joint effects of the random telegraph and static noises

Abstract: In the present paper, the joint effects of two kinds of classical environmental noises, without direct interaction among each other, on the dynamics of quantum correlations (QCs) of a three-qubit system coupled in independent environments is investigated. More precisely, we join the random telegraph noise (RTN) and the static noise (SN) and focus on the dynamics of entanglement and quantum discord (QD) when the qubits are initially prepared in the GHZ- and W-type states. The overall noise affecting the qubits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 64 publications
2
30
6
Order By: Relevance
“…3 and 7. In comparison, the current results under both mixed noisy configurations differ completely from those defined in [91] for joint dephasing effects of static and random telegraph noise. In addition, the qualitative dynamical behaviour of the entanglement, purity, and decoherence coincides with one another and with previous findings.…”
Section: Detailed Time Evolution Analysiscontrasting
confidence: 80%
See 3 more Smart Citations
“…3 and 7. In comparison, the current results under both mixed noisy configurations differ completely from those defined in [91] for joint dephasing effects of static and random telegraph noise. In addition, the qualitative dynamical behaviour of the entanglement, purity, and decoherence coincides with one another and with previous findings.…”
Section: Detailed Time Evolution Analysiscontrasting
confidence: 80%
“…The slopes decay faster as the value of g increases, indicating the dephasing nature of the parameter. We also find the current dephasing effects under the current mixed noisy situation completely different from that of the non-Gaussian noises, such as of random and static nature investigated in [47,48,61,88,89].…”
Section: B Power-law Noise Maximized Configurationmentioning
confidence: 63%
See 2 more Smart Citations
“…In recent year, the dynamics of quantum correlations in the situation where quantum systems are affected by environments describes classically (i.e., model by means of a classical Gaussian or non-Gaussian distributed random field) has been an active area of research [6,7,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and many interesting results have been obtained. In particular, it has been shown that when three qubits are coupled to an external classical noise such as random telegraph noise [16][17][18], static noise [20] and colored noise [19,21] in a common environment, quantum correlations among them survive indefinitely.…”
Section: Introductionmentioning
confidence: 99%